Physician estimates of the feasibility of preserving the dying for future revival - Ariel Zeleznikow-Johnston; Emil F. Kendziorra; Andrew T. McKenzie (PLoS ONE, 2026)
Objectives To assess US physicians’ estimates of the feasibility of preservation procedures (cryopreservation, aldehyde-based fixation) for enabling future revival, their views on clinical interventions to improve preservation outcomes, and their positions on ethical and legal frameworks surrounding these end-of-life options. Design Cross-sectional survey conducted October 2025. Setting Sermo, an online platform for verified US healthcare professionals. Participants 334 physicians comprising 150 primary care physicians (general practice, internal medicine, family medicine) and 184 other specialists. Main outcomes and measures Estimated probability that preservation retains neurally-encoded information sufficient for future revival; support for pre-mortem anticoagulation and pre-cardiac arrest procedure initiation; views on compatibility with patient-centered care. Results Among 334 physicians, the median estimated probability that preservation under ideal conditions could retain sufficient neural information for future revival was 25.5%. Overall, 27.9% found preservation somewhat or very plausible for enabling future revival; 47.0% found it somewhat or very implausible. Most physicians (70.7%) supported prescribing anticoagulants to terminal patients to improve preservation quality; 11.7% opposed. For patients choosing preservation in combination with medical assistance in dying, 44.3% supported initiating preservation prior to cardiac arrest; 28.8% opposed. Most (58.1%) agreed preservation could be consistent with compassionate care (20.1% disagreed), and 49.1% reported comfort with patients choosing preservation (30.0% uncomfortable). Familiarity with preservation correlated with higher probability estimates (ρ = 0.26; p < 10 −3 ), while end-of-life discussion frequency correlated with support for pre-cardiac arrest procedures (ρ = 0.18; p = 0.003). Conclusions US physicians assigned a median 25.5% probability to preservation retaining neural information under ideal conditions in a manner potentially compatible with future patient revival. The majority support for pre-mortem anticoagulation and plurality support for pre-cardiac arrest initiation indicate that many physicians would consider accommodating patient requests for preservation-enhancing interventions. These findings may inform development of clinical guidelines, though the speculative nature of the estimates warrants consideration.